Pengaruh Internal Locus Of Control, Environment dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa - Irma Nur Naini; Putri Ulfa Kamalia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to analyze the influence of internal locus of control, environment and entrepreneurship education on the entrepreneurial interest of Unesa PE Study Program students.The type of correlational research with a quantitative approach used in this research and the sample was 130 students. Technical analysis applies multiple linear regression analysis and classical assumption tests. The results of this research are that there is an internal locus of control influence on the entrepreneurial interest of Unesa PE Study Program students, there is no environmental influence on the entrepreneurial interest of Unesa PE Study Program students, there is an influence of entrepreneurship education on the entrepreneurial interest of Unesa PE Study Program students, and there is a joint influence of Internal locus of control, environment, and entrepreneurship education on the entrepreneurial interest of Unesa PE Study Program students. This is evidenced by the results of simultaneous tests there is an influence together with the magnitude of the significance value of 0.000<0.05. The partial test results of the internal locus of control variable have an effect with a magnitude for a value of 0.000<0.05 Environment has no effect on the magnitude for a significance value of 0.088>0.05. Entrepreneurship education has an effect with a magnitude for a significant value of 0.000<0.05. In conclusion, internal locus of control and entrepreneurship education significantly influence business interests, but the environment does not affect business interests. Keywords: Internal Locus of Control, Environment, Entreprenuership Education, Entrepreneurial Interes.